Feeding with poly(I:C) induced long-term immune responses against bacterial infection in turbot (Scophthalmus maximus) - Jing He (Elsevier, 2021)
Poly(I:C) is a kind of chemosynthetic double-stranded RNA (dsRNA) analogue which could act as TLR3 agonist and induce IFN production. It is widely applied in anti-virus treatment and immunoregulation, as well as vaccine adjuvant in farmed animals. However, whether poly(I:C) could activate innate immune response to defense against bacterial infection remains unclear. In this study, we established a feeding trial model with different dose of poly(I:C) in turbot larvae, then challenged with Edwardsiella piscicida after 3–7 weeks resting period. The results show that feeding turbot with poly(I:C) exhibited a stronger inflammatory response and antioxidant stress ability, and significantly elevated the survival rate within the decreased bacterial loads. Importantly, the bacterial infection-induced white feces in hindgut of turbot were significantly alleviated after poly(I:C) feeding, and this administration induced protection could last for about 7 weeks. Taken together, these findings indicate that feeding turbot with poly(I:C) could enhance a long-term intestinal mucosal immunity in response to bacterial infection, suggesting that poly(I:C) might be a promising immunostimulant in aquaculture.